Analysis of Cost Budget Plans in Disaster Logistics Warehouse Planning of the Badan Penanggulangan Bencana Daerah (BPBD) Bantul Regency, D.I. Yogyakarta - Alfinur Insaniyati Umi Sa'adah; Sely Novita Sari; Rizal Maulana (Universitas Islam Raden Rahmat, Malang, 2025)
From the various roles of the Bantul Regency BPBD in managing disaster preparedness and response in the Bantul area, which is known to be prone to disasters, the construction of a disaster logistics warehouse is needed to support the implementation of disaster management. To ensure the effectiveness and efficiency of the construction of the warehouse, an analysis of the Cost Budget Plan (CBP) is needed. The purpose of this study is to analyze the costs needed to complete the construction of the Bantul Regency BPBD logistics warehouse. The types and sources of data used are secondary data in the form of floor plan drawings, cut drawings, and detailed drawings. The method carried out is by analyzing the price of the unit of work using the applicable units of goods and services. CBP is obtained from the product of the volume of work multiplied by the result of the unit price of work. CBP analysis on the Bantul BPBD Logistics Warehouse Planning was obtained of Rp 20,026,590,027. The results of this study help to ensure appropriate budget allocation, prevent cost overruns, and become the main guideline in project implementation to support effective disaster response by BPBD.